Measuring The Performance of Humanitarian Supply Chains and Problems of Their Application in Practice - Dusan REPIK; Pavel FOLTIN (Communications of International Proceedings, 2022)
This study examines the development of logistics performance measurement in the Czech Red Cross supply chain to address the increasing variability and frequency of disasters. Practical knowledge of Czech Red Cross logistics managers was used for the study. Based on this, performance indicators were developed for further testing in practice.
Keywords: Humanitarian supply chain; performance; KPI; humanitarian logistics